Strong Dependence of Atmospheric Feedbacks on Mixed‐Phase Microphysics and Aerosol‐Cloud Interactions in HadGEM3. (19th June 2019) - Bodas‐Salcedo, A.; Mulcahy, J. P.; Andrews, T.; Williams, K. D.; Ringer, M. A.; Field, P. R.; Elsaesser, G. S.
Abstract: We analyze the atmospheric processes that explain the large changes in radiative feedbacks between the two latest climate configurations of the Hadley Centre Global Environmental model. We use a large set of atmosphere‐only climate change simulations ( amip and amip‐p4K ) to separate the contributions to the differences in feedback parameter from all the atmospheric model developments between the two latest model configurations. We show that the differences are mostly driven by changes in the shortwave cloud radiative feedback in the midlatitudes, mainly over the Southern Ocean. Two new schemes explain most of the differences: the introduction of a new aerosol scheme and the development of a new mixed‐phase cloud scheme. Both schemes reduce the strength of the preexisting shortwave negative cloud feedback in the midlatitudes. The new aerosol scheme dampens a strong aerosol‐cloud interaction, and it also suppresses a negative clear‐sky shortwave feedback. The mixed‐phase scheme increases the amount of cloud liquid water path (LWP) in the present day and reduces the increase in LWP with warming. Both changes contribute to reducing the negative radiative feedback of the increase of LWP in the warmer climate. The mixed‐phase scheme also enhances a strong, preexisting, positive cloud fraction feedback. We assess the realism of the changes by comparing present‐day simulations against observations and discuss avenues that could help constrain the relevant processes. Key Points: Large changes in shortwave cloud feedbacks exist between two recent configurations of Met Office model Changes in midlatitude feedbacks explain most of the global‐mean differences The new aerosol and mixed‐phase schemes explain most of the feedback differences